2022
DOI: 10.3390/min12080944
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of the Role of Combined Bulk Micro- and Nano-Bubbles in Quartz Flotation

Abstract: Bulk micro-nano-bubbles (BMNBs) have been proven to be effective at improving the flotation recovery and kinetics of fine-grained minerals. However, there is currently no research reported on the correlation between the properties of BMNBs and flotation performance. For this purpose, aqueous dispersions with diverse properties were created by altering preparation time (0, 1, 2, 3, 5, and 7 min), aeration rate (0, 0.5, 1, 1.5, and 2 L/min) and aging time (0, 0.5, 1, and >3 min). Micro- and nano-bubbles were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…We have used the data presented in [32] to produce the illustrative example shown in Figure 1 of the approximate frequency distribution of bubbles by size, which demonstrates that NB concentrate in the size range of 0.05 -0.5 µm, MB concentrate in the range of 10 -1000 µm, whereas in the range of 1-10 µm there are practically no bubbles. This fact suggests that it is possible to separate NB from MB by the sedimentation of the latter, as was done in [31,33]. Recent theoretical studies [34][35][36] have shown that the existence of stable NBs and their absence in the region of 1-10 μm can be attributed to the ratio of opposing capillary and electrostatic forces.…”
Section: Nano-bubble Generationmentioning
confidence: 84%
See 1 more Smart Citation
“…We have used the data presented in [32] to produce the illustrative example shown in Figure 1 of the approximate frequency distribution of bubbles by size, which demonstrates that NB concentrate in the size range of 0.05 -0.5 µm, MB concentrate in the range of 10 -1000 µm, whereas in the range of 1-10 µm there are practically no bubbles. This fact suggests that it is possible to separate NB from MB by the sedimentation of the latter, as was done in [31,33]. Recent theoretical studies [34][35][36] have shown that the existence of stable NBs and their absence in the region of 1-10 μm can be attributed to the ratio of opposing capillary and electrostatic forces.…”
Section: Nano-bubble Generationmentioning
confidence: 84%
“…The efficiency of combined micro-and nano-flotation of quartz particles of the size of below than 60 µm has been explored in [33]. And the findings have demonstrated that the simultaneous application of NB and MB have improved the recovery of quartz recovery from 72 to 79%.…”
Section: Experimental Datamentioning
confidence: 99%
“…During the flotation process, the impeller speed and air flow rate were set to 1000 rpm and 40 mL/min. Details of flotation operation procedures can be found in previous literature. , The froth products were recovered with four time intervals (0–0.5, 0.5–1, 1–2, and 2–4 min(s)) for a total flotation time of 4 min. All flotation products were collected and dried in a dryer (at 100 °C for 120 min) to determine their weight, mass recoveries, and kinetics.…”
Section: Methodsmentioning
confidence: 99%
“…Nanobubbles (NBs) possess unique physicochemical properties, including large specific surface area, low terminal velocity, and long lifetimes, making them attractive for enhancing mineral flotation [33,34]. It is important to note that some of the literature defines NBs as both micro-scale and nano-scale bubbles [35][36][37]. Furthermore, there are two types of NBs used in mineral flotation: bulk and surface NBs [38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%